Epstein–Barr virus gene expression and latency pattern in gastric carcinomas: a systematic review. (March 2017) - Ribeiro, Joana; Oliveira, Cláudia; Malta, Mariana; Sousa, Hugo
Methods: A systematic review of literature was conducted to identify all published reports regarding the expression of Epstein–Barr Virus (EBV) proteins/transcripts and EBV latency patterns in EBV-associated gastric carcinomas (EBVaGC).Results: The literature search retrieved 247 papers, of which 25 papers matched the inclusion criteria. The analysis reveals that the most frequently expressed EBV latent proteins are EBNA1 (98.1%) and LMP2A (53.8%), while LMP1 and LMP2B are present in only 10% of cases. Lytic proteins, such as BARF0 and BARF1, and other lytic transcripts are present in almost half of cases.Conclusion: EBVaGC seems to display a unique transcription/latency pattern that does not fit the 'standard' EBV latency patterns and therefore should be further studied to better understand EBVaGC carcinogenesis.